Alternative Lithographic Technologies IV 2012
DOI: 10.1117/12.916311
|View full text |Cite
|
Sign up to set email alerts
|

Pattern scaling with directed self assembly through lithography and etch process integration

Abstract: Directed self-assembly (DSA) has the potential to extend scaling for both line/space and hole patterns. DSA has shown the capability for pitch reduction (multiplication), hole shrinks, CD self-healing as well as a pathway towards line edge roughness (LER) and pattern collapse improvement [1][2][3][4]. The current challenges for industry adoption are materials maturity, practical process integration, hardware capability, defect reduction and design integration. Tokyo Electron (TEL) has created close collaborati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…Prepattern material is required to have some special properties such as surface free energy control, solvent resistance to the solvent of BCP solution, thermal resistance on BCP anneal, etching resistance on pattern transfer, and so on. In previous works, guiding pattern materials such as silicon oxide 8 and negative tone development resist 11 have been reported. We selected SOC as a guiding material from a cost and etching resistance point of view.…”
Section: Introductionmentioning
confidence: 99%
“…Prepattern material is required to have some special properties such as surface free energy control, solvent resistance to the solvent of BCP solution, thermal resistance on BCP anneal, etching resistance on pattern transfer, and so on. In previous works, guiding pattern materials such as silicon oxide 8 and negative tone development resist 11 have been reported. We selected SOC as a guiding material from a cost and etching resistance point of view.…”
Section: Introductionmentioning
confidence: 99%
“…[10,25] The template was treated with a brush polymer by spin-coating a hydroxyl-terminated brush material from a suitable solvent followed by a hotplate bake at 150 °C for 1 minute. The coated substrate was then annealed at 250 °C for 20 minutes under nitrogen on a hotplate.…”
Section: Chemoepitaxymentioning
confidence: 99%
“…Application of DSA for semiconductor devices is line/space and hole pattern. Many studies are demonstrated to construct their fabrication techniques 1,2 . Morphology of line and hole depends on process conditions.…”
Section: Introductionmentioning
confidence: 99%